2019
DOI: 10.31234/osf.io/tw4bd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Premenstrual Disorders: A Primer and Research Agenda for Psychologists

Abstract: Females are two times more likely to develop an affective disorder and three times more likely to make a suicide attempt. The etiology of these sex differences is complex, and cannot be reduced to biology alone. However, the growing field of reproductive mood disorders highlights how lifetime exposure to fluctuations in neuroactive sex hormones (including across the menstrual cycle) do contribute to greater female risk, specifically among those females who are neurobiologically sensitive to normal hormone chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…A range of disorders of the menstrual cycle have significant implications for physical, mental, and social well-being. 39 In addition, other difficulties associated with the menstrual cycle impact quality of life including pain, physical discomfort, impacts on mental health, 40 , 41 and abnormal uterine bleeding. 42 These may occur in the absence of disorders of the menstrual cycle.…”
Section: Defining Menstrual Healthmentioning
confidence: 99%
“…A range of disorders of the menstrual cycle have significant implications for physical, mental, and social well-being. 39 In addition, other difficulties associated with the menstrual cycle impact quality of life including pain, physical discomfort, impacts on mental health, 40 , 41 and abnormal uterine bleeding. 42 These may occur in the absence of disorders of the menstrual cycle.…”
Section: Defining Menstrual Healthmentioning
confidence: 99%
“…In addition, several studies using behavioral tasks have documented perimenstrual reductions in inhibitory control and associated cortical activity for some hormone‐sensitive women (for a review, see Owens & Eisenlohr‐Moul, 2018). Studies with younger participants have found similar perimenstrual elevations in self‐reported impulsive behavior among those with high trait‐level impulsivity (Roberts et al, 2018) or high borderline personality disorder traits (reviewed in Eisenlohr‐Moul, 2019), but no studies of adolescents have examined within‐person changes in inhibitory control across the cycle using behavioral measures. In addition, deficits of inhibitory control have been identified as a potential risk factor in the transition from suicidal thoughts to suicidal behavior, particularly among adolescents (e.g., Glenn & Nock, 2014).…”
Section: An Emerging Framework For Perimenstrual Suicide Risk In Adolescencementioning
confidence: 99%
“…The perimenstrual phase is associated with increases in negative affect, including depressed mood, anxiety, mood lability, and anger/irritability among women with PMDD. It is also associated with worsened mood among women with depressive disorders (reviewed in Eisenlohr‐Moul, 2019) and hormone‐sensitive adolescents (Buddhabunyakan et al, 2017; Czajkowska et al, 2015). Naturally, within‐person increases in negative affect are associated strongly with increases in adolescent girls’ suicidal thoughts and behaviors (e.g., Nock, Prinstein, & Sterba, 2010).…”
Section: An Emerging Framework For Perimenstrual Suicide Risk In Adolescencementioning
confidence: 99%
See 2 more Smart Citations